2022
DOI: 10.3389/feduc.2022.841385
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perceptions of Their Role and Classroom Management Practices in a Technology Rich Primary School Classroom

Abstract: This case study investigates primary school teachers’ perceptions of their role and practices regarding classroom management in technology-rich classrooms. The data was collected through individual and focus group interviews, observation and a survey at a school where implementation of digital technologies has been a high priority over several years. The study identifies complexity and contemporary elements in teachers’ perceived role and practices, as the rapid evolution of ICT requires teachers to constantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…While Scott and Nakamura (2022) highlight the importance of effective instruction, Marzano and Marzano (2003) emphasize that the teacher-student relationship is an essential foundation for effective classroom management. With their focus on classroom management in technology-rich classrooms, Johler et al (2022) also confirmed the critical importance of leadership, good teacher-student relationships, and teacher adaptability in taking on the role of a learner. Effective approaches to classroom management are characterized by a focus on proactive, preventive procedures rather than reactive ones (Korpershoek et al, 2016).…”
Section: Defining Concepts Of Classroom Managementmentioning
confidence: 76%
“…While Scott and Nakamura (2022) highlight the importance of effective instruction, Marzano and Marzano (2003) emphasize that the teacher-student relationship is an essential foundation for effective classroom management. With their focus on classroom management in technology-rich classrooms, Johler et al (2022) also confirmed the critical importance of leadership, good teacher-student relationships, and teacher adaptability in taking on the role of a learner. Effective approaches to classroom management are characterized by a focus on proactive, preventive procedures rather than reactive ones (Korpershoek et al, 2016).…”
Section: Defining Concepts Of Classroom Managementmentioning
confidence: 76%
“…It provides a perception of the role of faculties regarding the discipline in classroom management. It also identifies the contemporary complexity of faculties in maintaining competency despite the issues inside the classroom to facilitate the learning process, (Johler, et al, 2022). Hence, it also shows that the promotion of good methods in classroom discipline provides a procedure for consistent, fair, and positive discipline to determine class acceptability in terms of behavior of students which means the process of discipline has increased the decision-making of faculties for better learning output.…”
Section: Resultsmentioning
confidence: 96%
“…Berkembangnya teknologi informasi memberikan dampak perubahan pada berbagai aspek kehidupan, salah satunya pada sistem pendidikan (Zhao et al, 2020), selain pertumbuhan teknologi informasi, pandemic covid 19 juga menjadi salah satu faktor mempercepat evolusi sistem pendidikan menuju sistem yang berbasis digital (Hikmawati et al, 2021) ; (Singh, 2022). Implementasi kebijakan pendidikan berbasis digital adalah suatu bentuk pengaplikasian media teknologi dalam sistem pendidikan pada seluruh aspek pendidikan baik dalam sistem pengajaran, penilaian, manajemen sekolah, maupun pengembangan profesionalisme guru dalam upaya menguatkan mutu pendidikan (Johler et al, 2022) ; (Andita & Rafaela, 2023) Oleh karena itu, penyelenggaran pendidikan berbasis digital merupakan strategi yang digunakan oleh manajemen suatu sekolah untuk menciptakan peserta didik yang terampil dan inovatif karena dapat meningkatkan keterampilan dan kemampuan siswa di era digital Dede & Richards (2012), mengembangkan pemikiran logis dan ketrampilan komunikasi (Machekhina, 2017).…”
Section: A Pendahuluanunclassified